2016
DOI: 10.2166/hydro.2016.180
|View full text |Cite
|
Sign up to set email alerts
|

Big data and hydroinformatics

Abstract: Big data is popular in the areas of computer science, commerce and bioinformatics, but is in an early stage in hydroinformatics. Big data is originated from the extremely large datasets that cannot be processed in tolerable elapsed time with the traditional data processing methods. Using the analogy from the object-oriented programming, big data should be considered as objects encompassing the data, its characteristics and the processing methods. Hydroinformatics can benefit from the big data technology with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Large-scale model outputs (e.g., multiple configurations of MODFLOW, Fienen et al, 2018;the National Water Model, Hooper et al, 2017;climate models, Scher, 2018), remote sensing data (e.g., Karpatne et al, 2016;Schaeffer et al, 2018), and hybrid modeled/observed gridded data sets (e.g., NLDAS, Mitchell, 2004) are the "big data" foundation for water resources (Y. Chen & Han, 2016), and the volume of direct in situ observations is small by comparison. Even the "richest" case of observations used in the study presented here included hundreds (not thousands or millions) of daily profiles for training (Figure 2).…”
Section: 1029/2019wr024922mentioning
confidence: 99%
“…Large-scale model outputs (e.g., multiple configurations of MODFLOW, Fienen et al, 2018;the National Water Model, Hooper et al, 2017;climate models, Scher, 2018), remote sensing data (e.g., Karpatne et al, 2016;Schaeffer et al, 2018), and hybrid modeled/observed gridded data sets (e.g., NLDAS, Mitchell, 2004) are the "big data" foundation for water resources (Y. Chen & Han, 2016), and the volume of direct in situ observations is small by comparison. Even the "richest" case of observations used in the study presented here included hundreds (not thousands or millions) of daily profiles for training (Figure 2).…”
Section: 1029/2019wr024922mentioning
confidence: 99%
“…In particular, DL can extract the spatio-temporal structure and characteristics of data, and it is a good solution to the problem of strong time dependence such as rainfall simulation and prediction. However, machine learning also has some challenges, such as the cost of big data and interpretability [122,123]. The cost of a big data platform is high, and only when the cost of data collation and cleaning is low can the advantages of big data be maximized.…”
Section: Extending Machine Learning Capabilitiesmentioning
confidence: 99%
“…The access to ARD has transformed how remote sensing is processed for FEWSs. Chen and Han [59] developed a Flood Prevention and Emergency Response System (FPERS) based on GEE. In the preflood stage of the FPERS, a huge amount of geospatial data is integrated into the system and categorized as typhoon forecast and archive, disaster prevention and warning, disaster events, and analysis, or basic data and layers.…”
Section: Progress In Big Data and Cloud Computingmentioning
confidence: 99%